Uji Kualitas Kertas Seni Dari Alang - Alang Dengan Konsentrasi Pelarut Naoh Dan Lama Pemasakan Yang Berbeda - Wulandari, Lina Astria Tri; , Dra. Aminah Asngad, M.Si (2017)
Art paper or can be called recycled paper is paper that can be used as materials for handicrafts. Usually made from crop wastes that contain high fiber. alang - alang is a plant that is not utilized menggandung high fiber which can be used as raw material for paper making art. Such materials are processed using NaOH solvent. The purpose of this study was to determine the quality of the art paper alang - alang using NaOH and long ripening solvent different. With research parameter test tensile strength, tear strength, and organoleptic test (texture, color, fiber appearance, and acceptance of the community). This study used an experimental method with a completely randomized design (CRD) with two factors, one is the concentration of NaOH (K), K1 = 5%, K2 = 10%, K3 = 15% and a factor of 2 is long ripening (L), L1 = 60 minutes, L2 = 90 minutes with 6 treatments. The results showed the highest tensile strength and tear on the treatment K1L1 worth 1.69 N/mm2 for tensile strength and 1.75 N for tear strength. The test results of sensory texture dominant rude just on treatment K3L1 and K3L2 show smooth texture, appearance fibers more dominant kuranng looked only at treatment K2L1 show appearance fibers are not visible, the color is more dominant whitey only on treatment K3L1 and K3L2 russet and panelists Like on this paper.